A microtubule-interacting protein involved in coalignment of vimentin intermediate filaments with microtubules - Dráberová, E; Dráber, P (Journal of cell science, 1993)
A protein of M(r) 210,000 was identified in 3T3 cells by immunoblotting and by immunoprecipitation with a monoclonal antibody MA-01. The protein was thermolabile and was located on 3T3 microtubules prepared by taxol-driven polymerization in vitro. On fixed cells the MA-01 antigen was located on interphase and mitotic microtubular structures, vinblastine paracrystals, taxol bundles and colcemid-resistant microtubules. Microinjection experiments with purified MA-01 antibody followed by double immunofluorescence have shown that the injection of antibody led to disruption of vimentin filaments, whereas the distribution of cytoplasmic microtubules was unchanged. The collapse of vimentin filaments started 30 minutes after injecting the antibody at immunoglobulin concentrations 2 mg ml-1 or higher and reached its maximum 3-6 hours after the injection. Within 20 hours after the injection vimentin filaments became reconstituted. Microinjection of the antibody into cells pre-treated with vinblastine resulted in localization of the MA-01 antigen on vinblastine paracrystals as well as on coiled vimentin filaments. The data presented suggest that the MA-01 antigen is a new microtubule-interacting protein that mediates, directly or indirectly, an interaction between microtubules and vimentin intermediate filaments.
Keywords: Antigens; paclitaxel; mikrofilamenta; antigeny; monoklonální protilátky; Microinjections; Microtubules; kompartmentace buňky; Demecolcine; Antibodies, Monoclonal; Mice; buňky 3T3; Actin Cytoskeleton; Microtubule-Associated Proteins; proteiny asociované s mikrotubuly; mikrotubuly; 3T3 Cells; zvířata; fluorescenční protilátková technika; vimentin; Cell Compartmentation; myši; Fluorescent Antibody Technique; Vinblastine; demekolcin; Paclitaxel; Vimentin; mikroinjekce; vinblastin; Animals